A functional BCI model by the P2731 working group: psychology. Issue 3 (3rd July 2021) - Zapała, Dariusz; Hossaini, Ali; Kianpour, Mazaher; Sahonero-Alvarez, Guillermo; Ayesh, Aladdin
ABSTRACT: The development of Brain-Computer Interfaces (BCI) gathers experts and specialists in various fields, such as engineering, computer science, medicine, or cognitive neuroscience. Each of these disciplines has specific terminology, which makes mutual understanding and research collaboration difficult. The IEEE P2731 working group aims to improve communication between BCI researchers by developing a functional model and standards for terminology that can be used as a common description framework for all the involved knowledge fields. This work focuses on the vocabulary of mental processes involved in BCI communication and describes their role in a Functional Model that considers their influence on BCI performance. Finally, it presents potential uses of the proposed model.